The importance of student preparedness factors for clinical training: comparing the opinions of faculty veterinary academics and practice-based preceptors in three veterinary schools with workplace-based remote distributed models of clinical training - Cockcroft, Peter D.; Price, Bonnie E.; Barr, Margeret C. (Research in veterinary science, 2025)
Clinical training preparedness is defined as the degree of competency of a veterinary student to work and learn at an expected level. The aim of this study was to quantitatively investigate the level of importance and agreement attached to each of 91 clinical training preparedness factors by practice-based clinical supervisors and faculty veterinary academics in three veterinary programmes with remote distributed models of workplace-based clinical training. The data was collected using an online questionnaire from academics and preceptors at the School of Veterinary Medicine, University of Surrey; the College of Veterinary Medicine, University of Arizona; and the College of Veterinary Medicine, Western University of Health Sciences. The participants were requested to rate each factor according to an ordinal five-point impact Likert scale. Impact was defined as how much effect a factor would have on a student being able to learn and participate. There were 115 preceptor and 44 academic responders. There was a high level of agreement between the preceptors and academics within, between and across each of the three schools for the factor rating mean, median and mode values. The impact on learning and engagement were all rated moderate or higher. The outcomes of this quantitative survey provide strong evidence that the student preparedness factors investigated were considered important by the preceptors and the academics. When adopting the preparedness framework within the curriculum it is important that academics, preceptors and students share a common understanding of what preparedness for clinical training means. •Clinical training preparedness is defined as the degree of competency to work and learn at an expected level.•Preparedness enables learning opportunities to be maximised and the stress of transitioning to be minimised.•The agreement between the practice-based preceptors and faculty-based academics for the 91 preparedness factors was high.•The factors were all rated as having a moderate or higher impact on student learning and engagement.